Articulated robotic system-wireless, manual and shadow mode. (2021) - Devendran, P.; Prasath, S.; Mohanan, Smeya; Praveen, G.
Abstract: The current availability of industrial Robot is communicated through specific programming for specific applications; if a change in operation is required then Human intervention for coding is essential. This Technique incorporates the usage of sensors that are being present in the Smart phone. Hence external sensing device is not essential to make wireless communication. Our system allows taking control over the robot by the means of two modes(i.e., ) Manual and Gesture Mode. MANUAL MODE provides the feature of controlling as well as teaching the robot and also has the capability of performing the actions that have been taught(i.e., ) Teach pendant facility for the user. GESTURE MODE is to transmit human Gestures to the bot by means of Axis Control. Both of these Actions are transmitted to kit through Wireless modem. As this system is Scalable and portable it can undertake small-end Domestic applications to commercial large-end applications. In case of any change in operation, there is no need for manual intervention to change the code. This application enables the user to quickly teach the robot to a new process within a short span of time. Hence our Robot works under Multi-purpose domain.